Evaluation of the Effect of Oxygen-Helium Mixture on the Severity of Cough in Patients with Coronavirus Infection - K. A. Tsygankov; R. E. Lakhin; A. V. Shchegolev; A. D. Zhdanov; A. G. Klimov (Вестник анестезиологии и реаниматологии, 2022)
The objective: to evaluate the effect of inhalation of heated oxygen-helium mixture on the severity of cough in patients with coronavirus infection (COVID-19).Subjects and Methods. A single-center randomized prospective study was conducted. Group 1 (control) (n = 32) included patients who received standard COVID-19 therapy. Group 2 (n = 29) included patients who had inhalations with heated oxygen-helium mixture (OHM) in addition to standard treatment. The severity of cough was assessed using 6-point scale (0 ‒ no cough; 1 ‒ single cough impulse; 2 ‒ rare cough during the day; 3 ‒ frequent cough that does not affect daytime activity, 4 ‒ frequent cough that reduces daytime activity due to cough; 5 ‒ severe cough in which daytime activity is impossible), and respiratory rate (RR) was also for 7 days from the moment of inclusion in the study.Results. Cough symptoms of varying severity were detected in all patients included in the study. A prolonged coughing fit led to decrease in blood oxygen saturation. In the control group, intensive cough persisted for the first 4 days and subsequently decreased with the favorable course of the disease. In the group, where OHM was used, on the 3rd day, the severity of cough decreased to 2 scores compared to the initial 4 scores (p = 0,005). The use of OHM allowed reducing the severity of cough versus traditional therapy. The analysis of intergroup comparisons showed differences starting from day 3 (p = 0.014): in patients of Group 2 (with the use of OHM), cough was mostly rare during the day, at the same time, frequent cough persisted in patients of the control group according to assessment of the severity of daytime cough. When analyzing RR, it was revealed that in Group 2, RR from day 2 was below the one in the control group, in which no changes were detected during the entire observation period.Conclusion. The use of inhalation of oxygen-helium mixture allows reducing the intensity of cough and respiratory rate in patients with COVID-19.